2006
DOI: 10.1128/jcm.44.5.1834-1835.2006
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of the Value of Quantitative Culture of Organisms from Blood Collected through Central Venous Catheters in Differentiating between Contamination and Bloodstream Infection

Abstract: Collection of blood through a central venous catheter for the diagnosis of bacteremia is a debated topic. Quantitative cultures of organisms from blood collected through central venous catheters were found to be highly sensitive, specific, and predictive of bacteremia, especially when a cutoff point of 15 colonies of skin organisms was used.Drawing of blood through a central venous catheter (CVC) for the diagnosis of bacteremia is highly debated (2,4,(11)(12)(13)15) due to the possibility of culturing blood co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 15 publications
0
8
1
1
Order By: Relevance
“…Diagnosis of true CoNS bloodstream infection becomes particularly difficult when only a single blood culture sample is obtained (4)(5)(6)(7)(8)(9)(10)(11). We previously reported that a cutoff point of Ͼ15 CFU/ml and positive clinical findings were useful for differentiating culture samples representing true bacteremia from contaminated blood culture samples (2). Furthermore, QBCs are not widely performed in all hospitals and may not be routinely available to clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of true CoNS bloodstream infection becomes particularly difficult when only a single blood culture sample is obtained (4)(5)(6)(7)(8)(9)(10)(11). We previously reported that a cutoff point of Ͼ15 CFU/ml and positive clinical findings were useful for differentiating culture samples representing true bacteremia from contaminated blood culture samples (2). Furthermore, QBCs are not widely performed in all hospitals and may not be routinely available to clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with central venous catheter (CVC) lines, catheterrelated bloodstream infections (CRBSIs) were defined as follows: (1) the culture of a specimen of purulent drainage from the insertion site grew CoNS that had the same resistance pattern as the culture strain from the peripheral blood; (2) the semiquantitative culture of the removed CVC tip revealed ≥15 colony-forming units by the roll plate technique [14]; (3) indicative differential time to positivity (i.e., the blood culture obtained through an intravascular catheter became positive at least 2 h earlier than a positive simultaneous blood culture obtained from a peripheral vein [15]). Surgical wound infection was defined according to the definitions of the Centers for Disease Control and Prevention (CDC) [16].…”
Section: Foci Of Bacteremiamentioning
confidence: 99%
“…Febrile high-risk patients, such as the critically ill patients or patients with cancer, may often have blood cultures contaminated with CoNS from the hands of medical personnel or the catheter hub, particularly if the blood specimens are drawn from the CVC [26,27]. Use of strict criteria for the definition of CoNS bacteremia that include 2 blood cultures positive for CoNS as well as high quantitative blood cultures (115 CFU/ mL) has been shown to be important for distinguishing true CoNS bacteremia from contaminated blood cultures [2,[20][21][22][23]. Furthermore, use of strict criteria for CRBSI, as per the IDSA guidelines, is necessary to attribute true CoNS bacteremia to the catheter rather than other sources that could exist in patients with cancer who have long-term catheters in place [17].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the clinical signs and symptoms of infection (fever, chills, rigors, or hypotension), true CoNS CRBSI was defined on the basis of the following 3 criteria, which are predictive of true bacteremia: (1) at least 2 blood cultures, from any source, should be available for all patients [2,[20][21][22]; (2) at least 1 blood culture should yield a quantitative blood count of у15 CFU/mL [23]; and (3) the blood samples that yielded positive culture results should have been collected within a 72-h period [24]. Bacteremia also had to fulfill the definition criteria of the IDSA for probable or definite CRBSI [17].…”
Section: Clinical Characteristicsmentioning
confidence: 99%